Diagnostic implications of the double deficit model for young adolescents with dyslexia. (7th November 2019) - Harrison, Allyson G.; Stewart, Matthew
Abstract : Considerable support exists for both the phonological core deficit and the naming speed deficit models of dyslexia. The double deficit model proposed that many students with dyslexia might also be impaired in both underlying processes. Employing either performance thresholds (i.e., scores below the 16th or 25th percentile) or k ‐means clustering as classification methods, the current study investigated whether 154 young adolescents with dyslexia could be categorized into subtypes according to the presence or absence of phonological deficits alone, naming speed deficits alone, or a combination of the two and whether group composition changed depending on classification method. Results support the existence of both single and double deficit groups and confirm that those with both deficits are the most severely impaired across multiple measures. Contrary to previous research, most adolescents were classified as either naming speed only (about a third of the group) or double deficit when defining impairment using performance thresholds to classify groups. This may suggest that although early phonological deficits are amenable to remediation, identification of language symbols fails to become automatized in most individuals with dyslexia and may require more targeted intervention. Classification differences reported in the literature may depend on age and methods employed for classification.